Undergraduate Students’ Perspectives on the Reference Transaction: A Pilot Study - de Jong, Cees-Jan (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
A qualitative user study examining the reference transaction role in four undergraduate students’ information seeking process. Data was obtained through interviews, which were analyzed using a grounded theory approach. Findings show that participants sought no process intervention from reference librarians, had negative perceptions of the reference transaction, and valued independence during the research process. Une étude qualitative des utilisateurs examinant le rôle du processus de référence lors des recherches d’information de quatre étudiants de premier cycle. Les données ont été obtenues à l’aide d’entrevues analysées avec l’approche de la théorie ancrée. Les résultats montrent que les participants n’ont par cherché à obtenir d’aide de la part des bibliothécaires de référence, qu’ils ont des perceptions négatives à l’endroit du processus de référence, et qu’ils valorisent l’indépendance durant le processus de recherche.